Highlighting Photocatalytic H2-Production from Natural Seawater and the Utilization of Quasi-Photosynthetic Absorption as Two Ultimate Solutions for CO2 Mitigation - Wenfeng Wang; Xi Chen; Heng Zhang; Changqing Jing; Yifan Zhang; Bo Yan (International Journal of Photoenergy)
This paper reviews five potential solutions for CO2 mitigation and theoretically analyzes related outstanding questions. Emission trading under the global mitigation objectives and policies is in dilemma because reducing emission while utilizing fossil fuels is a difficult balance. CO2 capture and sequestration (CCS) technique offers a comprehensive solution, but it is risky and expensive. Analyses of the 100% renewable energy plan suggest hydrogen as a fuel of zero CO2 emission. Photocatalytic splitting of natural seawater can be an ultimate scheme for the hydrogen production, providing that the associated technological constraints would be overcome. Soil CO2 absorption in the arid regions (terms such absorption “quasi-photosynthetic absorption”) implies a potential solution, but the kinetics and overall importance are undetermined. Further investigations of these unresolved issues are strongly needed to realize the global CO2 mitigation target. Comparing the five potential solutions, photocatalytic H2-production from natural seawater and the utilization of quasi-photosynthetic absorption are highlighted as two ultimate solutions.